GIG ECONOMY: PERILAKU KEPUASAN PENGEMUDI OJEK ONLINE PADA LAYANAN PENGIRIMAN RESTORAN CEPAT SAJI - Apriliani, Ernolita Kartika; Ariani, Mintarti; Setyaningrum, Idfi (FEB Universitas Sam Ratulangi Manado, 2023)
Abstract. The aim of this research is to determine the level of satisfaction of online motorcycle taxi driver partners in Surabaya. The research method used is a quantitative method with data collection through questionnaires using a Likert scale. This study uses the dimensions of service quality at a fast food restaurant in Surabaya using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) data analysis methods. The results showed that the overall satisfaction level of online motorcycle taxi driver partners at a restaurant in Surabaya based on the Customer Satisfaction Index (CSI) method obtained results of 82.86% in the